Entre el Estallido social y la disputa Constituyente: una aproximación gramsciana a la crisis de hegemonía acaecida en el “laboratorio” neoliberal chileno (1973-2021) - Cabrera, Andrés (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
This article aims to offer an analysis of the political crisis in Chile, considering the organic causes of the popular uprising that arose in October 2019, the evolution of the constitutional process, and the results of an unusual electoral cycle that has been favourable to the political advance of the left and social movements in the course of two volatile years. To explain this political context, it is crucial to understand the general features of an entire historical cycle that seems to be coming to an end. This cycle began with the coup d'état against the government of Salvador Allende on September 11, 1973, and continued with the establishment of a neoliberal model and a constitutional order during Augusto Pinochet’s dictatorship. These have remained in place since the return to democracy and civil government in 1990. A period of stability ensued, lasting until roughly 2011. However, since then the social legitimacy of the political party system has been subject to systematic degradation due to entrenched corruption and the rise of new social movements. In order to problematize the ongoing Chilean crisis, this approach combines three research dimensions. First, the reception of Antonio Gramsci’s work in Chile, which runs parallel to this entire historical cycle. Second, the use of the concepts of ‘relations of force’ and ‘crisis of hegemony’ in Gramsci’s Prison Notebooks. And third, the local interpretations of contemporary Chilean political history. Retrospectively, it is possible to understand the current Chilean crisis as a problem of ‘exhaustion’ in three key structural dimensions: the neoliberal model, the constitutional order, and the political consensus. In the context of this crisis of hegemony, the left and social movements have gained the advantage in the electoral battlefield during the last two years. They overwhelmingly won in the plebiscite of October 2020. Later, their dominance at the polls allowed them to secure prominent positions within the Constitutional Convention in the May elections of 2021. And finally, the candidate of the left coalition Apruebo Dignidad, Gabriel Boric, also won the presidential election in the run-off of December 2021. The last stage of this constitutional and electoral cycle will end with a plebiscite in the second part of 2022 that will confirm or reject the proposal of the Constitutional Convention. Chilean neoliberalism; Gramsci reception; Crisis of hegemony; Constitutional Disputes.